2021
DOI: 10.1109/access.2021.3099633
|View full text |Cite
|
Sign up to set email alerts
|

Mining Subsidence Monitoring With Modified Time-Series SAR Interferometry Method Based on the Multi-Level Processing Strategy

Abstract: The supply of coal is related to the stability of social development in China. Coal mining faces are generally located under farmland and wasteland to avoid destroying the livelihood and property of residents, which seriously affects the selection of permanent scatterer (PS) with time-series interferometric synthetic aperture radar (TS-InSAR) method. The advanced TS-InSAR (ATS-InSAR) method combining PS and distributed scatterer (DS) monitoring modules is a useful tool to increase measurement points. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To verify the monitoring results of different methods (MCTSB-InSAR, CAESAR-InSAR, and the improved method), the linear regression analysis is carried out on the deformation rates of completely coincident points in the whole study area. The correlation coefficient r is used to measure the degree of close correlation between the two methods [29], [42], as shown in Figure 10. Assuming that  and  represent the deformation rates obtained by two different methods, their correlation coefficient P can be expressed as ( ) ( ) ( )…”
Section: A Verification Of Monitoring Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the monitoring results of different methods (MCTSB-InSAR, CAESAR-InSAR, and the improved method), the linear regression analysis is carried out on the deformation rates of completely coincident points in the whole study area. The correlation coefficient r is used to measure the degree of close correlation between the two methods [29], [42], as shown in Figure 10. Assuming that  and  represent the deformation rates obtained by two different methods, their correlation coefficient P can be expressed as ( ) ( ) ( )…”
Section: A Verification Of Monitoring Resultsmentioning
confidence: 99%
“…To obtain the detailed damage information caused by land subsidence, dangerous assessment and area statistics are performed based on the results of the improved method. Previous studies have shown that there are different dangerous assessment indexes in different areas and actual conditions [42][43][44]. In this paper, areas with deformation rate less than -10 mm/yr are considered as dangerous areas, which are classified into four groups.…”
Section: B Damage Caused By Land Subsidencementioning
confidence: 99%
“…Interferometric Synthetic Aperture Radar (InSAR) is a remote sensing method capable of dynamic ground deformation monitoring with the advantage of large scale, high resolution, and high accuracy [10,11]. With the development of Muli-Temporal InSAR (MT-InSAR) technology [12][13][14][15][16], shortcomings (temporal decorrelation and atmospheric delay) of traditional InSAR methods have been overcome [17][18][19][20][21]. The two polular MT-InSAR methods are persistent scatterer InSAR (PS-InSAR) and small subset InSAR (SBAS-InSAR).…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned modern observation techniques have been widely used in surface deformation monitoring. Many scholars have contributed to the comprehensive understanding of surface deformation by improving observation accuracy through data acquisition and data processing methods [21][22][23][24][25][26][27][28]. Meanwhile, many studies simultaneously use one or two traditional measurement techniques and modern techniques to study and analyze surface subsidence, but few studies combine the advantages of various techniques for analysis [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%